Speech Act Analysis in Nurse-Patient Communication - Mulyani, Mulyani; Syamsinar, Syamsinar (STAIN MAJENE, 2025)
In the medical field, communication between nurses and patients is essential since it can influence patients' comprehension of medical situations and adherence to therapy. With an emphasis on the many kinds of illocutionary speech acts and their pragmatic meanings, this study attempts to investigate speech acts utilized in nurse-patient communication. This study employs a qualitative research method and descriptive approach. The study, which was carried out at Daya Hospital in Makassar, revealed the many speech acts—representative, directive, expressive, declarative, and commissive—that nurses and patients employ when communicating. Nurses commonly use directive speech actions when communicating with patients in order to provide care and take action. Patients commonly use expressive speech acts to express all of their feelings, illnesses, and concerns. Appropriate and effective speaking actions can benefit patients and nurses, speed up the healing process, and create a pleasant environment.